Preservice Elementary Teachers Conceptions and Self-Efficacy for Integrated STEM - Deepika Menon; Deef A. A. Shorman; Derek Cox; Amanda Thomas (MDPI AG, 2023)
Educational reform efforts have emphasized preparing highly competent and confident preservice teachers to deliver effective K-12 Science, Technology, Engineering, and Mathematics (STEM) instruction. Self-efficacy is a key variable that influences motivation and performance, and therefore it is necessary to support the development of preservice teachers' integrated STEM teaching self-efficacy. This mixed-methods study investigates how preservice elementary teachers' integrated STEM teaching self-efficacy is shaped during their participation in a newly redesigned STEM semester consisting of three concurrent methods courses (science and engineering, mathematics, and technology methods courses). The quantitative data sources included the Self-efficacy for Teaching Integrated STEM instrument administered as a pre- and post-test, demographic, and open-ended questionnaire. The qualitative data sources included STEM identity letters, integrated STEM models, and STEM growth reflections. Quantitative results showed statistically significant positive gains in integrated STEM-teaching self-efficacy from the beginning to the end of the semester. The results from the content analysis also revealed positive shifts in PSTs' conceptions and attitudes about STEM. Notably, having a similar discourse across the three parallel-running methods courses provided a suitable context for preservice teachers to develop a shared understanding of integrated STEM. Implications for preservice STEM teacher preparation and research are discussed.